Condiciones para el uso del celular en un caserío de los Andes: implicancias para la educación remota (Revista Peruana de Investigación Educativa, 2024)
Based on the data of an ethnography carried out with the families of a rural village in the Andes of Huanuco, in this article I analyze the strategies that families use to appropriate cell phones in the context of the geographic and socioeconomic conditions they face. The findings show that all the aspects involved in the use of the cell phone present challenges for these families, from obtaining the mobile device to those related to its operation, such as charging the batteries of their equipment, obtaining the mobile credit and capturing the signal. These conditions affect families, men and women in a different way, and within the framework of an increasingly neoliberal system that shapes the political economy of cell phones in this rural village. At the same time, the findings of this study reveal the set of strategies that families have deployed to overcome the obstacles they encounter. I conclude the article by discussing the implications of these findings for remote education in rural areas.
Keywords: Cell phones, access, living conditions, agency, rural environment